Pelatihan Mengelola Homestay di Desa Wisata Donokerto - Damasdino Damasdino (Jurnal Abdimas Pariwisata, 2020)
Managing Homestay Training in the Tourism Village of Donokerto. Donokerto Village is one of the pioneering tourist villages that has quite a good potential in terms of the diversity of tourist attractions. In addition to tourist attractions, as the main factor triggering a visit, Homestay is one of the main sources of income which is very strategic to be taken into account in every management of a tourist village. Remembering Homestay is a basic need for every tourist who wants to visit to enjoy the attraction of the village in a long time As a tourism village that is being pioneered, Donokerto Village does not yet have human resources or a community that understands the ins and outs of Homestay management. Therefore, AMPTA Yogyakarta College of Tourism in collaboration with PUM Netherlands Senior Experts held community service with the theme "Training of Managing Homestays in Donokerto Village". The community service activities were carried out using the presentation method and then followed by a panel discussion. The recommendation from this community service activity is that proper homestay management is a crucial factor in creating a safe, comfortable and tourist-friendly tourist village. For this reason, it is expected that the community in managing homestays must meet the criteria for aspects of products, services, and management